Electrochemical water oxidation using a copper complex. Issue 31 (28th June 2018) - Nestke, Sebastian; Ronge, Emanuel; Siewert, Inke
Abstract : This study highlights the importance of proton coupled electron transfer (PCET) during electrochemical-driven water oxidation catalysis employing a copper complex. Abstract : Herein, we report the application of the mononuclear copper complex1, [Cu II (L)] 2+, in electrochemical water oxidation catalysis (L = 1, 3-bis(((1-methyl-1 H -imidazol-2-yl)methyl)amino)propan-2-ol). The complex exhibits a N4 donor set consisting of two amine and two imidazole units and a dangling OH unit in close proximity to the copper ion.1 exhibits a moderate apparent rate constant k cat of 0.12 s −1 in catalysis and operates at an overpotential of 0.83 V. Detailed investigations allowed us to derive a mechanism for water oxidation. The catalysis proceeds only under basic conditions, where [Cu II (L)(OH)] +, 1 H−1, is the main solution species, which indicates that a negatively charged ligand is necessary to drive the catalysis. Initial oxidation of1 H−1 is coupled to proton loss forming a copper(iii ) species and further oxidation initiates oxygen evolution. Initial oxidation of1 under neutral, i.e. non-catalytic, conditions is pH independent, highlighting the importance of PCET steps during catalysis. We collected reasonable evidence that catalysis proceeds via a water nucleophilic attack mechanism. The electrolyte presumably acts as a proton acceptor in catalysis as the onset potential depends on the buffer employed.